Mechanistic Study of the Effects of Magnesia Reactivity on Setting and Hardening of Basic Magnesium Sulfate Cement - Miao, Meng; Wu, Chengyou; Yu, Hongfa; Tan, Yongshan (Journal of Advanced Concrete Technology, 2020)
Basic magnesium sulfate (BMS) cement was prepared by magnesia with different reactivities derived from calcination of basic magnesium carbonate at 600 to 1000°C. The effects of reactivity of magnesia on the setting time and compressive strength of BMS cement was investigated. Furthermore, XRD, SEM, MIP, hydration heat evolution and the pore solution composition were used to analyze the action mechanism of magnesia reactivity. The results show that the main strength phase of 5Mg(OH)2•MgSO4•7H2O (5•1•7 phase) was formed in BMS cement prepared by magnesia with calcination temperature higher than 600°C. The magnesia with a high BET surface area and low crystallite dimension showed a high adsorption capacity for citrate ions in magnesium sulfate solution, decreasing their concentration in the pore solution. By acting as a soft template for 5•1•7 phase formation, the decrease in citrate ions resulted in a low amount of 5•1•7 phase, forming Mg(OH)2 instead, leading to a low-strength BMS cement.